2022
DOI: 10.1101/2022.06.29.496132
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Paracrine signaling by pancreatic δ cells determines the glycemic set point in mice

Abstract: Pancreatic islets contain several endocrine cell types that coordinate to maintain blood glucose homeostasis. While beta and alpha cells are thought to be the main drivers of glucose homeostasis through insulin and glucagon secretion respectively, the contribution of delta cells and somatostatin (SST) secretion to establishing the glycemic set point remains unresolved. Here we remove local SST signaling from delta cells within the pancreatic islet to investigate their contribution to the glycemic set point. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“…It has indeed been demonstrated that paracrine secretion of ATP from primary b-cells occurs at 3mM glucose and enhances secretion (65), although we do not know whether this ATP release also occurs in EndoC-bH cells. In more general terms, our observation may pinpoint to the crucial role of d-cells in native islets, which are absent in these spheroids, in setting the glucose threshold (66). Notably, in EndoC-bH5 cells a biphasic pattern of electrical activity was apparent upon glucose stimulation, which is a hallmark of primary islets (15) and such a pattern had also been reported in dynamic insulin secretion assays of EndoC-bH5 cells (9).…”
Section: Discussionsupporting
confidence: 71%
“…It has indeed been demonstrated that paracrine secretion of ATP from primary b-cells occurs at 3mM glucose and enhances secretion (65), although we do not know whether this ATP release also occurs in EndoC-bH cells. In more general terms, our observation may pinpoint to the crucial role of d-cells in native islets, which are absent in these spheroids, in setting the glucose threshold (66). Notably, in EndoC-bH5 cells a biphasic pattern of electrical activity was apparent upon glucose stimulation, which is a hallmark of primary islets (15) and such a pattern had also been reported in dynamic insulin secretion assays of EndoC-bH5 cells (9).…”
Section: Discussionsupporting
confidence: 71%
“…We did not quantify the total β cell mass by multiplying the relative insulin-positive area with pancreas weight. But, important for our study is that the islet area and β cell contribution to islets did not show any significant sex-specific differences and therefore we can assume a similar islet cell paracrine modulation (75)(76)(77)(78).…”
Section: Discussionmentioning
confidence: 71%
“…We, therefore, performed a four-week washout to allow the replenishment of intestinal SST + cells without Lepr ablation before performing any phenotypical examinations. While the regeneration of islet delta cells from an unrecombined progenitor population rarely occurs, intestinal D cells regenerate within two weeks, while gastric D cells demonstrate apparent regrowth within four weeks and completely recover within three months ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…The transgenic Gcg-Cre exhibits silencing, with recombination in only 30-45% of alpha cells, and the inducible gene replacement Gcg-Cre ERT2 line suffers from glucagon haploinsufficiency ( 58 ). Somatostatin, Sst-Cre , and the Sst-rtTA used here are all expressed in gut enteroendocrine D cells, hypothalamic neurons, and the motor cortex ( 50 ).…”
Section: Discussionmentioning
confidence: 99%